Optimalisasi Pengendalian Persediaan Produk Perishabel di UMKM - Abdul Kodir Jaelani, Akmal; Chandrahadinata, Dody; Andriyas Kurniawan, Wahyu (Jurnal Kalibrasi, 2025)
Ikbal Cuanki MSME faces inventory control problems due to seasonal demand fluctuations and production limitations, especially during the lean season and Ramadan. This study uses a quantitative approach with a seasonal Economic Order Quantity (EOQ) model based on data from July 2024 to June 2025. The results show that the optimal order quantity during normal, abundant, and lean seasons is 1,359 kg per order (9 orders per month), while during Ramadan it increases to 1,800 kg per order (9 orders per month). EOQ has been proven to reduce inventory costs and minimize the risk of excess stock. However, supporting strategies such as frozen storage, warehouse optimization, and supplier contracts are still necessary.